The investigation and characterisation of colourless glass from forensic and archaeological contexts using multiple interdisiplinary analytical techniques - Scott, R. (Department of Engineering and Applied Sciences, 2011)
The techniques used to analyse glass in forensics and archaeology differ: forensic analysis relies almost completely on Refractive Index, whereas archaeology uses compositional analyses. This thesis focuses on examining, explaining and challenging those differences through the analysis of colourless glass from forensic and archaeological contexts. Two major studies are undertaken, one focussing on stained and painted glass from Christ Church Cathedral, Oxford, and one based on modern automotive glass. The analytical techniques common to each discipline are applied to the samples of glass used in the research. The studies each focus on individual research questions; the Christ Church study investigates the 17th century Van Linge window scheme, the compositions of fragments of glass from throughout the cathedral’s history are investigated, and shown to separate into distinct compositional groups. The study also successfully recreates the Van Linge window scheme; and the historical and compositional analyses allowed the study of one of the in-situ painted windows in the cathedral. The automotive glass study investigates the complex relationship between glass manufacturers and vehicle manufacturers. The research revealed that certain makes of vehicle were beginning to group and glass from specific areas of the world was also grouping together. This study highlights the potential use for glass as a tool for intelligence gathering rather than just as evidence. The application of the different analytical techniques to each study is discussed along with the merits of using each of the techniques. The potential of using forensic techniques in archaeology and archaeological techniques in forensics is evaluated. Specifically, LA-ICP-MS, which is rarely used in forensics, could be an innovative and potentially important tool for the forensic evaluation of cars and other glass evidence. A discussion of the research and databases needed to make the most of the techniques is assessed.